Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree - Rodriguez-Calcerrada, Jesus; Jaeger, Carsten; Limousin, Jean M; Ourcival, Jean M; Joffre, Richard; Rambal, Serge (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.
Keywords: abiotic factor; canopy depth; Carbon; drought acclimation; mediterranean habitat; nonstructural carbohydrates; thermal acclimation; throughfall exclusion